Environmental Sanitation, Personal Hygiene, STH Co-infection in TB Patients (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Globally, helminthiasis is one of the infectious diseases that are often associated with the incidence of tuberculosis. Helminth co-infection modulates the immune system of TB patients by reducing Th-1 response that functions as protector against Mycobacterium tuberculosis. This condition disrupts the process of eliminating bacteria so that its development becomes more progressive. The impact is the activation of latent TB and the success of TB treatment. A Soil-transmitted Helminth (STH) is a group of intestinal worms that often infect humans. Previous studies prove that environmental sanitation and personal hygiene are risk factors associated with STH infection. The study to determine the relationship of environmental sanitation and personal hygiene with the incidence of STH co-infection in TB patients at Puskesmas Puger, Jember in September until December 2019. This study uses a cross-sectional design. The sampling technique uses total sampling. A total of 32 TB patients met the criteria as study sample. The data analysis uses Fisher Test. Results showed the prevalence of STH co-infection was relatively low (18.8%); most of the respondents had good environmental sanitation and personal hygiene conditions. Bivariate analysis showed p-value (0,476) for environmental sanitation and p-value (1,000) for personal hygiene. This study concludes that there is no correlation between environmental sanitation, personal hygiene, and STH co-infection in TB patients at Public health center in Puger.